The profitability and production of a beef herd on transitional Cymbopogon- Themeda veld, receiving three different levels of lick supplementation - Preliminary results - Foster, L.A.; Fourie, P.J.; Neser, F.W.C. (South African Journal of Animal Science, 2014)
The importance of containing costs through the optimal utilization of feed emphasizes the need to optimize, rather than maximize, the rate of reproduction. It is, however, unknown which lick supplementation regimen, provided to an extensive beef herd on mixed veld, could bring about the most profitable and efficient farming enterprise. The aim of the study was thus to determine what lick supplementation regime would be most profitable in an extensive beef production system maintained on transitional Cymbopogon-Themeda veld. The different lick supplementation regimens offered differed in crude protein (CP) content, percentage non-degradable protein (NDP), metabolisable energy (ME) content, and recommended daily intake. A herd of Drakensberger cows and heifers was divided into three treatment groups (Treatment A, Treatment B and Treatment C), with 70 animals (n = 70) per treatment group. The CP, NDP, ME content of the licks provided in Treatment A were higher than those provided in Treatment B and C, while the CP, NDP, ME content of the licks provided in Treatment B were higher than those provided to Treatment C, but lower than those provided to Treatment A. The first two years’ (2011 - 2012 and 2012 - 2013) preliminary results indicate no significant differences in parameters that affect cow herd performance (weaning weight, cow herd pregnancy rate, intercalving period) between treatments. However, substantial cost differences in the lick supplied between treatments was recorded; thus, affecting profitability. Significant differences between treatments in the pregnancy rates of the first-calf heifers was recorded in the second year, and indicated that providing protein in a drought during summer to first calf heifers may increase the calving rate and hence profitability.
Published Article
Keywords: Beef cattle; cow herd production; extensive farming; lick supplementation; profitability